Republic of Palau : Assessment of the Supervision and Regulation of the Financial Sector-Volume II; Detailed Assessment of Observance of Standards and Codes. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper reviews key findings of the Detailed Assessment of Observance of Standards and Codes in the Financial Sector of Palau. The assessment reveals that there is a relatively low level of compliance with the Basel Core Principles for Effective Banking Supervision. Palau is compliant with one of the Core Principles, largely compliant with six and materially noncompliant with seven Core Principles. The status of legal protection for supervisors has been assessed as compliant, but is subject to an amendment to be passed by the Congress shortly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet